Prognostic value of the Geriatric Nutritional Risk Index in patients undergoing cardiac surgery: a systematic review and meta-analysis - Luo, Ping; Shi, Kai; Luo, Yu; Ren, Hai-Bo (Frontiers in Nutrition, 2025)
BackgroundThe Geriatric Nutritional Risk Index (GNRI) is a key indicator of nutritional status in elderly individuals. Poor nutritional status has been linked to unfavorable surgical outcomes, but its prognostic value in cardiac procedures remains uncertain. This meta-analysis investigates the relationship between the GNRI and prognosis in cardiac surgery patients.MethodsA comprehensive literature search was performed across the PubMed, Embase, and Web of Science databases. Studies were included if they evaluated preoperative GNRI and reported short-term mortality, long-term mortality, or major postoperative complications, such as acute kidney injury (AKI), wound complications, and infections. Risk ratios (RRs) and 95% confidence intervals (CIs) were calculated to compare outcomes between patients with low and normal GNRI. Heterogeneity was assessed using the I2 statistic, and a random-effects model was used to synthesize and analyze the results from the included studies.ResultsThe pooled results of 16 cohort studies involving 7,593 patients showed that a low preoperative GNRI was significantly associated with an increased risk of short-term mortality (RR: 3.19, 95% CI: 1.68–6.07, p < 0.001; I2 = 39%) and long-term mortality (RR: 2.32, 95% CI: 1.63–3.30, p < 0.001; I2 = 77%). Low GNRI was correlated with a higher risk of AKI (RR: 1.77, 95% CI: 1.11–2.81, p = 0.02; I2 = 74%) and overall infection (RR: 3.35, 95% CI: 2.01–5.57, p < 0.001; I2 = 29%), while no significant association was observed for wound complications, although this outcome was based on only four studies. Meta-regression identified mean age as a significant contributor to heterogeneity in long-term mortality (p = 0.04), while sample size explained part of the heterogeneity in short-term mortality (adjusted R2 = 23.5%).ConclusionA low preoperative GNRI is correlated with an increased risk of mortality and postoperative complications in cardiac surgery patients. Preoperative nutritional assessment using GNRI may identify high-risk patients.Systematic review registrationPROSPERO ID CRD42025637322.